Lack of viable parasites in cured 'Parma Ham' (PDO), following experimental Toxoplasma gondii infection of pigs. (September 2017) - Genchi, Marco; Vismarra, Alice; Mangia, Carlo; Faccini, Silvia; Vicari, Nadia; Rigamonti, Sara; Prati, Paola; Marino, Anna Maria; Kramer, Laura; Fabbi, Massimo
Abstract: Twelve Large White pigs were experimentally infected with 1000 Toxoplasma gondii oocysts/each. Serology was carried out at different time points post infection (p.i.) and animals were slaughtered at four months p.i. One of two thighs was examined for T. gondii infection status by PCR and bioassay in mice. The other thigh was processed for Parma ham production. Four thighs were examined after twelve months of curing, four after fourteen months and four were examined after sixteen months. Cured hams were analyzed by PCR, bioassay and in-vitro cultivation on Vero cells followed by real-time PCR. Pigs seroconverted from day 21 p.i. Bioassays were positive for all fresh thighs, but negative for cured hams. PCR was positive for parasite DNA from most thighs both at slaughter and post curing, but parasite growth was not observed following in vitro cultivation and real-time PCR. Results indicate that the curing process of Parma Ham (PDO), when carried out according to the Parma Ham consortium regulations, can inactivate T. gondii tissue cysts. Results would suggest that food-borne transmission of T. gondii to consumers from Parma ham can be excluded. Highlights: Parma ham ("Prosciutto di Parma") is one of the most important DOP products in Italy. Pigs were experimentally infected with oocysts of a Type II strain of T. gondii . Hams were cured according to consortium guidelines and analyzed for viable parasites. No hams were positive by either bioassay or in vitro culture and real-time PCR. Certified Parma ham is safe for consumers at risk for T. gondii infection.